The quest for strategic Malaysian Quality National Primary School Leaders - Mohd Ali, Hairuddin (Emerald, 2012)
Purpose – The purpose of this paper is to investigate the nine-point strategic leadership characteristics of Malaysian Quality National Primary School Leaders (QNPSL) and to indicate the implications of these findings for the current educational management and leadership practices in their quest for Malaysian quality education.